Gerakan Literasi Pada Anak Usia Dini Melalui Outdoor Learning Activity - Sumini, Ni Komang; Andari, Ida Ayu Made Yuni (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The implementation of the literacy movement through outdoor learning activities is done in an integrated manner, meaning that these activities can be carried out in the subjects, not fixated on Indonesian literacy or English literacy. Children can recognise letters and numbers while playing outside the classroom, creating an exciting and fun atmosphere. The literacy movement aims to develop students' character and aims to instil a culture of literacy in students to create lifelong learning. The literacy movement has several specific objectives, namely; Firstly, promoting a culture of literacy. Secondly, increasing the capacity of educated citizens and the school environment, and thirdly, making schools a fun and child-friendly learning park for school children to manage knowledge. Finally, the continuity of learning by presenting a variety of textbooks that suit different reading strategies. This study uses a descriptive qualitative approach to the process of implementing GELIS through outdoor learning activities in early childhood at Hooray School Denpasar.